(untitled) (Geo-Eco-Marina, 2020)
The Recent ostracod species Manawa staceyi Swanson, 1989, belonging to the superfamily Puncioidea, was originally considered a relict species related to the Palaeozoic Palaeocopa, ostracods, now extinct. During the last 30 years research on Manawa documented the basal position of the superfamily Puncioidea within the phylogenetic tree of the Subclass Podocopa. The Palaeocopa is possibly a heterogenous taxon containing both myodocopids and podocopids. Re-examination of the systematic position, phylogenetic affinities and evolution of the superfamily Puncioidea is presented using information from the comparative analysis of the body plans of Myodocopa and Podocopa, rationalised within morpho-functional modules: the carapace as a‘protective’ construct, the ambulatory complex, combined with feeding, reproductive and sensory systems. The significant traits of the different morpho-functional modules of the superfamily Puncioidea when compared to those of the ostracod Orders Podocopida and Platycopida suggest for the former group an independent phylogenetic position within the Subclass Podocopa, taxonomically treated as Order Punciocopida Schallreuter, 1968. Morphological traits such as the maxillulary endopodite and the 8th body limb of M. staceyi are considered deep genetic homologies existing within the Subclass Podocopa at the level of cellular regulatory systems. The widely gaping valves held in a ‘horizontal’ plane during the ambulatory activity and the collaborative structure and position of the 2nd antenna continued with respect to the 5th to 7th pair of limbs are considered solutions (adaptations) to psammobiotic life within the dynamic shallow marine habitats. Examination of the discrepancy between the low species diversity of Puncioidea and those of the species-rich nonmarine Cypridoidea may be as a result of the major differences in the way representatives of the two ostracod groups are able to actively perceive the surrounding environment as well as to their capacity to construct their niche, leading to successful speciation.